FASHION DESIGN,REFERENCED - KENNADI,ALICIA; Stoehrer, Emily Banis; Calderin, Jay. (AMERICA: ROCKPORT PUBLISHERS, 2013)
"Fashion Design, Referenced is a comprehensive guide through the art and industry of fashion design, richly illustrated with over 1,000 photographs and drawings. Within the framework of four central categories, Fashion Design, Referenced examines the many interwoven elements that form the tapestry of fashion."Fundamentals" provides an overview of the essential structure of the fashion profession (its organization, specializations, and centers) and looks at shifts in style over time and in ever-faster cycles going forward."Principles" introduces the steps in creating a collection, from design to production, and explores directions suggested by sustainability and technology."Dissemination" charts the many avenues by which fashion reaches its audience, whether on the catwalk or in the store, in print or online, in the museum or on the street."Practice" gathers and appraises the work of the most influential and innovative fashion designers of the twentieth and twenty-first centuries.From its first question--What is fashion design?--to its last--What does the future hold?--Fashion Design, Referenced chronicles the scope of ideas, inspirations, and expressions that define fashion culture.Visit the Fashion Design, Referenced Facebook page and become a fan at http://www.facebook.com/FashionDesignReferenced!"--
Includes index.
Keywords: Fashion; DESIGN / Fashion